Unusual presentation of a culture-positive right atrial mass - Sarma, Smita (2013)
We report a patient with a mass in the right atrium which led to pulmonary embolism. Postoperatively the mass was identified as a tuberculoma and it was culture-positive for Mycobacterium tuberculosis. Patient responded to modified antitubercular treatment and discharged from hospital in satisfactory condition.